Understanding the ultraviolet, green, red, near infrared and infrared emission properties of bismuth halide double perovskite. Issue 24 (9th November 2022) - Huang, Anjun; Liu, Mingzhe; Duan, Chang-Kui; Wong, Ka-Leung; Tanner, Peter A.
Abstract : Cs2 NaBiCl6 shows multi-luminescence properties at low temperature from the ultraviolet to infrared spectral regions, thereby demonstrating its potential application in the anti-counterfeiting field. Abstract : Lead-free double perovskite halides, notably the chlorides of bismuth, have received much interest in recent years due to the promising applications in the fields of solar cells and solid-state lighting. The blue, red and near infrared (NIR) emissions have been interpreted and assigned in many different ways in the literature. We present a combined theory-experimental approach to rationalize the understanding of the optical behaviour, using the model system Cs2 NaBiCl6 . First principles calculations highlight the major defects in this material by determining their formation energies under various conditions, as well as their optical excitation and emission energies. Samples of Cs2 NaBiCl6 were synthesized by three different methods, in addition to sodium and caesium depleted ones, and well-characterized. The blue, green, red, NIR and IR emission and excitation spectra and emission decay were measured from 298 K to 10 K and detailed interpretations have been made. Contrary to previous interpretations, all of the UV, visible and NIR emission originates from the initial excitation of trivalent bismuth. The blue and green emissions are from Bi 3+ or perturbed Bi 3+ species, whereas the exitonic red emission results from excited dimers, and the NIR emission from Bi 3+ at caesium sites. A new emission band at 1.4 μm is attributed to a color center and is observed for other hexachloroelpasolites using the present synthesis. Persistent luminescence decay is observed at 77 K and thermoluminescence indicates a trap depth of 0.18 eV. The quenching mechanisms of photoluminescence and the origin of persistent luminescence are explained. The outstanding luminescence properties enable the use of this material in anti-counterfeiting applications.